The Characteristic of a Literature Text (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
A literary text is an open literary-poetic system with many features, among which the signification, that is, its manifestation through a sign, and its structurality occupy a special place. It is these two aspects that express the essence of the text. Among hundreds of creative examples, only some - those that are perfect in terms of artistic merit - can reach the level of a literary text. The masterpieces of the prose work of the famous Uzbek writer Abdulla Kahhar have been elevated to such a high status.